PENGARUH DISIPLIN KERJA, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA KANTOR DESA MUNGGU KABUPATEN BADUNG - I Kadek Yoga Adi Antara; Anak Agung Dwi Widyani; Tiara Carina (VALUES, 2023)
High employee performance is very necessary in an organization to achieve the expected goals. With high performance, employees will try their best to overcome and solve problems faced in carrying out their duties and work. This research was carried out with the aim of finding out the influence of work discipline, work motivation and work environment on employee performance at the Munggu Village Office, Badung Regency. The population in this research was all employees in Munggu Village, Badung Regency. Totaling 35 people. The number of samples in this study was 35 people who were determined using the saturated sample method. The data in this research was obtained through the results of distributing questionnaires which were later analyzed using multiple linear regression analysis techniques. Based on the research results, it can be seen that: Work discipline, work motivation, and. The work environment has a positive and significant effect on employee performance at the Munggu Village Office, Badung Regency. Seeing the results of the research, it is recommended that the Head of Munggu Village, Badung Regency in the future should be able to implement strict sanctions for employees who commit violations. This is important to do to establish employee work discipline so that later employees can comply with all applicable rules. With high work discipline, employees will be able to work optimally and produce the best work results.